RETRACTED: Dynamics of MHD Convection of Walters B Viscoelastic Fluid through an Accelerating Permeable Surface Using the Soret–Dufour Mechanism - P. Anusha; M. Naga Swapna Sri; Vallabhaneni Venkata Venu Madhav; Ch. Sri Chaitanya; V.V. Spandana; Kuldeep K. Saxena; Dalael Saad Abdul-Zahra; Emanoil Linul; Chander Prakash; Dharam Buddhi; Raul Campilho (Applied Sciences)
The MHD convective Walters-B memory liquid flow past a permeable accelerating surface with the mechanism of Soret-Dufour is considered. The flow equation constitutes a set of partial differential equations (PDEs) to elucidate the real flow of a non-Newtonian liquid. The radiation thermo-physical parameters were employed based on the use of Roseland approximation. This implies the fluid employed in this exploration is optically thick. Utilizing suitable similarity terms, the flow equation PDEs were simplified to become total differential equations. The spectral homotopy analysis method (SHAM) was utilized to provide outcomes to the model. The SHAM involves the addition of the Chebyshev pseudospectral approach (CPM) alongside the homotopy analysis approach (HAM). The outcomes were depicted utilizing graphs and tables for the quantities of engineering concern. The mechanisms of Soret and Dufour were separately examined. The imposed magnetism was found to lessen the velocity plot while the thermal radiation term elevates the temperature plot because of the warm particles of the fluid.